Pregnancy in liver transplant recipients: A single center outcomes. Issue 10 (5th July 2018) - Turkyilmaz, Gurcan; Yasa, Cenk; Dural, Ozlem; Erturk, Emircan; Kalelioglu, İbrahim and Has, Recep and Yuksel, Atil
Abstract: Aim: Liver transplantation (LT) is the only effective treatment for the end‐stage liver disease. Although pregnancy after LT is considered to be safe, these patients are difficult to manage for obstetricians. In this study, we aimed to determine maternal and fetal outcomes in pregnancies after LT. Methods: We conducted a retrospective review of liver transplant recipients who had received prenatal care and delivered pregnancy at İstanbul University İstanbul Medical Faculty, Department of Obstetrics and Gynecology January 2010 and January 2017. Results: A total of eight pregnancies were identified during the study period. The mean age of the patients at the time of LT was 25.6 ± 5.3 years (range 19–36 years), and the mean age at conception was 30.1 ± 5.2 years (range 25–41 years). The mean interval between transplantation and conception was 54.2 ± 18.6 months (range 24–82 months). There was no a miscarriage or a stillbirth was observed in any of patients. Mean birth week was 37.2 ± 2.1 weeks and mean birthweight was 2852 ± 562 g (range 2150–3470 g). Three of eight deliveries (37.5%) occurred before 37 gestational weeks. Preeclampsia was detected in one patient, one pregnancy was complicated by intrauterine growth retardation and one case with gestational diabetes mellitus. Mean postnatal follow‐up period was 3.2 ± 2.4 years (range 1–7 years) and all of the babies were healthy. Graft rejection occurred in one patient after delivery. Conclusion: More favorable pregnancy outcomes can be achieved with a multidisciplinary team and satisfactory counseling is mandatory either preconception and through the pregnancy to reduce maternal‐fetal risks.